Reservoir design and operation: Effects on aquatic biota-a case study of planktonic copepods - Perbiche-Neves, Gilmar; Nogueira, Marcos Gomes [UNESP] (My University, 2013)
Copepod assemblages from two cascade reservoirs were analyzed during two consecutive years. The upstream reservoir (Chavantes) is a storage system with a high water retention time (WRT of 400 days), and the downstream one (Salto Grande) is a run-of-river system with only 1. 5 days WRT. Copepod composition, richness, abundance, and diversity were correlated with the limnological variables and the hydrological and morphometric features. Standard methods were employed for zooplankton sampling and analysis (vertical 50-μm net hauls and counting under a stereomicroscope). Two hypotheses were postulated and confirmed through the data obtained: (1) compartmentalization is more pronounced in the storage reservoir and determines the differences in the copepod assemblage structure; and (2) the assemblages are more homogeneous in the run-of-river reservoir, where the abundance decreases because of the predominance of washout effects. For both reservoirs, the upstream zone is more distinctive. In addition, in the smaller reservoir the influence of the input from tributaries is stronger (turbid waters). Richness did not differ significantly among seasons, but abundance was higher in the run-of-river reservoir during summer. © 2012 Springer Science+Business Media Dordrecht.
Keywords: Calanoida; Cyclopoida; Paranapanema River; Run-of-river reservoir; Storage reservoir; Zooplankton; community composition; compartmentalization; crustacean; design; hydrobiology; hypothesis testing; morphometry; reservoir; seasonality; turbidity; water retention; zooplankton; Brazil; Chavantes Reservoir; Salto Grande Reservoir; Sao Paulo [Brazil]